Hydrogen adsorption on WS2 decorated by Na and Li. (April 2019) - Sarvazad, Khatereh; Elahi, Mohammad; Ahmadian, Farzad; Boochani, Arash
Abstract: In this study, the effects of sodium and lithium decoration on the absorption of hydrogen molecules on the surface of the WS2 have been investigated. The first principles calculations based on the density functional theory showed that due to the larger binding energy of sodium and lithium atoms on the WS2 surface compare to the cohesive energy of these atoms in bulk, sodium and lithium will be distributed on a single-atom basis on the WS2 surface and will not come in the form of multi-atom clusters. The decoration of WS2 with sodium and lithium atoms leads to have conducting behavior. Absorbing hydrogen molecules on the surface of WS2, it was possible to absorb these atoms on the sodium and lithium-decorated WS2 surface, which showed that the lithium atom was able to absorb more hydrogen molecules and could be used as a promising substance in the storage area as well as the hydrogen gas sensor. Highlights: Larger binding energy of sodium and lithium atoms on the WS2 surface compare to the cohesive energy of these atoms in bulk. The decoration of WS2 with sodium and lithium atoms leads to this structure will be the conductor. The lithium atom was able to absorb more hydrogen molecules.